Elevated Neutrophil to Lymphocyte Ratio Associated With Increased Risk of Recurrent Vascular Events in Older Minor Stroke or TIA Patients - Chan, Ka Lung; Feng, Xueyan; Ip, Bonaventure; Huang, Shangmeng; Ma, Sze Ho; Fan, Florence S. Y.; Ip, Hing Lung; Huang, Li’an; Mok, Vincent C. T.; Soo, Yannie O. Y.; Leung, Thomas W.; Leng, Xinyi (Frontiers in Aging Neuroscience, 2021)
Background: The risk of recurrent stroke following a minor stroke or transient ischemic attack (TIA) is high, when inflammation might play an important role. We aimed to evaluate the value of neutrophil-to-lymphocyte ratio (NLR) in predicting composite cardiovascular events in patients with minor stroke and TIA. Methods: Consecutive patients with acute minor stroke or TIA admitted within 24 hours of symptoms onset during a 5-year period in a prospective stroke registry were analyzed. We calculated the NLR dividing absolute neutrophil count by absolute lymphocyte count tested within 24 hours of admission. NLR ≥ 4th quartile was defined as high NLR. A composite outcome was defined as stroke, acute coronary syndrome or vascular death within 1 year. We investigated associations between NLR and the composite outcome in univariate and multivariate analyses, among all patients and in those aged over 60 years (i.e., older patients). Results: Overall, 841 patients (median age 68 years; 60.4% males) were recruited. No significant independent association was found between NLR and the composite outcome in multivariate analysis in the overall cohort. Among the 612 older patients (median age 73 years; 59.2% males), the median NLR was 2.76 (interquartile range 1.96-4.00) and 148 (24.2%) patients had high NLR. The composite outcome occurred in 77 (12.6%) older patients, who were more likely to have a high NLR (39.0% versus 22.1%; p=0.001) than those without a composite outcome. In multivariate logistic regression, high NLR (adjusted odds ratio 2.00; 95% confidence interval 1.07-3.75; p=0.031) was independently associated with the composite outcome in older patients. Conclusions: In older patients with acute minor stroke or TIA, a higher NLR is an independent predictor of subsequent cardiovascular events, indicating inflammation as an important factor and potential therapeutic target for secondary prevention of such patients.